Economic growth, income inequality and poverty trends in pasture area’s householder in Sujanagar Upazila, Pabna, Bangladesh: implications for development strategy / Kazi Md.Barkat Ali and A.B.M Anamul Haque - Md.Barkat Ali, Kazi; Haque, A.B.M Anamul (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The paper based on the most recent primary household-level data obtained from a survey on income expenditure and poverty measures for 2019-20. A semi-structured questionnaire and 162 samples were administered. A simple random sampling technique was used in which secondary data were collected from primary, secondary and tertiary sources. Human development indicators for 1996 compare with the study area (Char and thorn area in Sujanagar Upazila, Pabna district, Bangladesh). The empirical result shows the analysis o f poverty, income inequality, economic growth & development scenario of pasture and thorn area in Sujanagar Upazila, Pabna district, Bangladesh. The paper aims to examine these householders who play an essential contribution to the national GDP, but their living level is below standard living. If these areas householder development access should be more available, they will return a great introduction to the society. This paper advised using antipoverty policy, the concept of poverty minimizing inequality that the community should be tolerated to attain the goal of minimizing poverty. It is helpful to distinguish between structural and transient causes of poverty. The provision of public goods plays a vital role in fighting poverty.